Validity Checking of the 3D Scanner Camera Noise Model - Kovács, Tibor (Acta Agraria Kaposváriensis, 2007)
The paper presents the development of an active triangulation laser scanner focusing on the line following algorithm. Assuming a video noise model the accuracy of the line following can be estimated based on the actual noise distribution parameters. The target of the paper is to validate the noise model with the installed system components. The measurement configuration is presented. The pattern set was recorded with this installation. The method for the validation of the components of the noise model is described in details.